Essence and Concept of Capitalization of Enterprises its Types and Methods of Evaluation - Pronko, Lyudmila; Kolesnik, Tatyana; Samborska, Oksana (European Journal of Sustainable Development, 2021)
The historical aspect of the development of scientists’ views on the company’s capitalization is studied in the work, the stages of development of the concept of cost-oriented management are determined. The role and place of market capitalization in the system of indicators of cost-oriented management are determined, modern methodical approaches to the assessment of the value of the enterprise taking into account the indicator of market capitalization are given. The fundamental differences between the areas of application of indicators of market value of the enterprise and market capitalization are established. The current problems of the Ukrainian economy that limit the widespread use of market capitalization in the valuation of companies are outlined, and proposals are made on the feasibility of valuing Ukrainian companies in terms of real capitalization. The importance of enterprise capitalization in the development of a market economy is emphasized. The evolution of the views of foreign scientists on the capitalization of enterprises has been studied. It is established that the economic essence of the capitalization of enterprises, as well as any asset, is the present value of future income generated by this asset. Bringing future income to the present is a process of discounting. The theory of capitalization of the company in its modern context began to be formed by neoclassical economists from the end of the XIX century. and gained popularity in the second part XX century. The theory of capitalization has given impetus to well-known neoclassical theories of corporate finance, such as the irrelevance theorem, risk theory, investment portfolio optimization theory, arbitrage pricing theory, and so on. It is established that according to the theory of capitalization, the capitalization of the enterprise and the market value of the enterprise are identical concepts, although the methods of their calculation differ. The theory of capitalization has given impetus to the development of many modern financial theories, which are currently under development and improvement.